2010
DOI: 10.1038/hr.2010.36
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin reduces oxidative stress and attenuates intermittent hypoxia-induced left ventricular remodeling in lean mice

Abstract: We have reported previously that intermittent hypoxia related to sleep apnea induces cardiovascular remodeling secondary to the oxidative stress. The aim of this study was to examine the effect of pitavastatin as an antioxidant to prevent intermittent hypoxia-induced left ventricular (LV) remodeling in mice without hypercholesterolemia. Eight-week-old male C57BL/6J mice (n¼35) were exposed to intermittent hypoxia (30 s exposure to 5% oxygen, followed by 30 s exposure to 21% oxygen) for 8 h per day during the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Then tumor necrosis factor-α (TNF-α and brain natriuretic peptide (BNP) mRNA were detected by performing RT-PCR under the following conditions: 50C for 2 min, 95C for 10 min, 40 cycles of 95C for 15 s, and 60C for 1 min. Expression of the target mRNAs was normalized for that of GAPDH mRNA (Inamoto et al, 2010).…”
Section: Quantitative Real-time Reverse Transcription-polymerase Chaimentioning
confidence: 99%
See 1 more Smart Citation
“…Then tumor necrosis factor-α (TNF-α and brain natriuretic peptide (BNP) mRNA were detected by performing RT-PCR under the following conditions: 50C for 2 min, 95C for 10 min, 40 cycles of 95C for 15 s, and 60C for 1 min. Expression of the target mRNAs was normalized for that of GAPDH mRNA (Inamoto et al, 2010).…”
Section: Quantitative Real-time Reverse Transcription-polymerase Chaimentioning
confidence: 99%
“…We previously demonstrated that chronic hypoxia accelerates the progression of atherosclerosis in apoE-KO mice Kato R, et al Ezetimibe and Cardiovascular Protection 6 (Nakano et al, 2005), while statin therapy reduces oxidative stress and attenuates left ventricular remodeling induced by intermittent hypoxia in mice (Inamoto et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Negative controls were processed with distilled water, and endometrium was used as the positive control. After cells were counterstained with Mayer's hematoxylin, TUNEL-positive cells were counted as described elsewhere (15).…”
Section: Animalsmentioning
confidence: 99%
“…A recent study showed that central obesity without OSA was not correlated with endothelial dysfunction, inflammation and increased oxidative stress. 9,10 There is a strong correlation between the extent of endothelial dysfunction and the severity of OSA. This is supported by evidence that OSA itself, but not obesity, induces vascular endothelial dysfunction and inflammation and also elevates oxidative stress (see Figure 1).…”
mentioning
confidence: 99%
“…2 Although co-founding variables made it difficult to directly link OSA and left ventricular hypertrophy, a close relationship between these two pathological conditions could dramatically and negatively impact patients' prognoses; therefore, molecular mechanisms that could establish a causal relationship between OSA and left ventricular hypertrophy should be more extensively studied. In this issue of Hypertension Research, Inamoto et al 10 examined the effects of statin therapy on intermittent hypoxia-induced left ventricular remodeling in mice, a known model for OSA. They reported that intermittent hypoxia-induced hypertrophy of the cardiomyocytes led to perivascular fibrosis and histological degeneration without affecting systemic blood pressure or plasma cholesterol.…”
mentioning
confidence: 99%